The relationship between heart functions and anemia in patients with end-stage renal disease receiving hemodialysis - Omar, Timor; Çağdaş, Metin; Artaç, İnanç and Karakayalı, Muammer and İliş, Doğan and Arslan, Ayça and Karabağ, Yavuz and Yesin, Mahmut and Avcı, Mustafa and Rencüzoğulları, İbrahim (The European Research Journal, 2024)
Objective: We investigated the relationship between anemia and cardiac functions by conventional and speckle-tracking echocardiography (STE) in patients with end-stage renal disease (ESRD) receiving hemodialysis. Methods: One hundred six patients with ESRD receiving hemodialysis were included in this cross-sectional study. The conventional echocardiography and STE findings were compared between the patients with and without anemia. In addition, a comparison of the findings between the ESRD patients and healthy controls consisting of 68 participants was conducted. Results: Compared to healthy controls, ESRD patients had lower left ventricular ejection fraction (LVEF), left ventricular global longitudinal strain (LVGLS), and left atrial reservoir strain (LASr) [53% (48-57) vs. 65% (62-68), -15.2 (-16.9˗ -13.6) vs. -19.7 (-16.9˗ -13.6), and -21.9 (-29.5˗ -15.3) vs. -29.9 (-35.3˗ -22.8), respectively, P-value <0.001 for all]. Of the ESRD patients, 70 (66%) had anemia. ESRD patients with anemia had higher interventricular septum (IVS), posterior wall (PW), and left atrial volume index (LAVi) values than patients without anemia. In addition, ESRD patients with anemia had lower LVEF, LVGLS, and LASr than patients without anemia [median (IQR), 13 (12-15) vs. 12 (11-14), P=0.004, 13 (12-15) vs. 12 (11-13.5), P<0.005, 43 (35-55) vs. 34.7 (28-50), P=0.013, 52 (48-55) vs. 56 (47.5-60), P=0.016, -14.6 (-16.4˗ -13.5) vs. -16 (-18.6˗ -14.7), P=0.003, and -21.6 (-30.5˗ -16.3) vs. -30.5 (-33.6˗ -23.3), P=0.006, respectively]. In multivariable logistic regression analysis, diabetes, PW, LASr, and LVGLS were independently associated with the presence of anemia in ESRD patients. Conclusion: Our study confirmed impaired cardiac mechanics in ESRD hemodialysis patients and showed that anemia was associated with further worsening cardiac mechanics in this population.